Unusual occurrence of domestication syndrome amongst African mole-rats: Is the naked mole-rat a domestic animal? - Serrano Nájera, Guillermo; Kin, Koryu (Frontiers in Ecology and Evolution, 2022)
The Naked mole-rat (NMR) is becoming a prominent model organism due to its peculiar traits, such as eusociality, extreme longevity, cancer resistance, and reduced pain sensitivity. It belongs to the African mole-rats (AMRs), a family of subterranean rodents that includes solitary, cooperative breeding and eusocial species. We identified and quantified the domestication syndrome (DS) across AMRs, a set of morphological and behavioural traits significantly more common and pronounced among domesticated animals than in their wild counterparts. Surprisingly, the NMR shows apparent DS traits compared to the solitary AMR. We argue that many of the NMR unconventional traits can be a side-effect of self-domestication. Animals can self-domesticate when a reduction of the fear response is naturally selected, such as in islands with no predators, or to improve the group’s harmony in cooperative breeding species. We propose that self-domestication was necessary to increase social tolerance during the evolution of cooperative breeding and eusociality among AMRs. Finally, we discuss how the DS traits are neutral or beneficial for the subterranean niche and how the increased social tolerance of self-domesticated species could be a side effect of the physical properties of the soil. Our hypothesis provides a novel avenue to enhance the understanding of the extraordinary biology of the NMR.